Social Support and Postpartum Depression in Acehnese Mothers - Maya Khairani; Zaujatul Amna; Nida Ul Hasanat; Muhana Sofiati Utami (Proceedings of the 1st International Conference on Social Science (ICSS), 2025)
Pregnancy and childbirth bring various changes that can make women vulnerable to postpartum depression. The consequences of women experiencing this disorder are not only limited to themselves but also have an impact on other individuals, such as their children or other children, spouses, and other family members. Social support is considered a key factor in reducing the risk of postpartum depression. This study aims to determine the role of social support on postpartum depression and the dynamics experienced by postpartum mothers. This study is a quantitative study with purposive sampling techniques. Data were collected through scales and open-ended questionnaires. In the first phase, 142 postpartum mothers completed two psychological scales (EPDS and MPSS). Based on the first phase, 84 mothers experienced symptoms of postpartum depression, and simple regression analysis showed that there was a role of social support in postpartum depression in mothers (F=11.249, p<0.001). Support from friends (p=0.02) and spouse (p=0.00) had a significant role in determining the mother's postpartum depression, while support from family (p=0.58) did not play a significant role. In the second phase, five postpartum women agreed to complete an open-ended questionnaire. Thematic analysis of the qualitative data showed three themes: symptoms of postpartum depression, postpartum activities, and social support.